2009
DOI: 10.1126/science.1178849
|View full text |Cite
|
Sign up to set email alerts
|

Positively Selected G6PD -Mahidol Mutation Reduces Plasmodium vivax Density in Southeast Asians

Abstract: Glucose-6-phosphate dehydrogenase (G6PD) deficiency--the most common known enzymopathy--is associated with neonatal jaundice and hemolytic anemia usually after exposure to certain infections, foods, or medications. Although G6PD-deficient alleles appear to confer a protective effect against malaria, the link with clinical protection from Plasmodium infection remains unclear. We investigated the effect of a common G6PD deficiency variant in Southeast Asia--the G6PD-Mahidol(487A) variant--on human survival relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
137
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(155 citation statements)
references
References 30 publications
10
137
1
Order By: Relevance
“…The difference in these estimates may be because they were based on different data, with that of Tishkoff et al (2001) based on microsatellite data and that of Slatkin (2008) based on sequence data. The selection coefficients and consequent times in Figure 1 are somewhat more consistent with that estimated by Tishkoff et al (2001) than the estimates of Slatkin (2008) and Louicharoen et al (2009). Carter and Mendis (2002) suggested that the original selective force for G6PD deficiency could have been either for resistance to P. falciparum or P. vivax.…”
Section: G6pd Deficiencysupporting
confidence: 70%
See 1 more Smart Citation
“…The difference in these estimates may be because they were based on different data, with that of Tishkoff et al (2001) based on microsatellite data and that of Slatkin (2008) based on sequence data. The selection coefficients and consequent times in Figure 1 are somewhat more consistent with that estimated by Tishkoff et al (2001) than the estimates of Slatkin (2008) and Louicharoen et al (2009). Carter and Mendis (2002) suggested that the original selective force for G6PD deficiency could have been either for resistance to P. falciparum or P. vivax.…”
Section: G6pd Deficiencysupporting
confidence: 70%
“…Tishkoff et al (2001) jointly estimated the age and selection for both A-and Med alleles using forward simulations and found that the estimated age of A-was 6357 years (254 generations) and the selection coefficient was 0.044, and that the estimated age of Med was 3330 years (132 generations) and the analogous selection coefficient was 0.034. From joint estimations using Bayesian methods, Slatkin (2008) estimated that the age of A-was only 1000 years (40 generations) and the selection coefficient was 0.25 and Louicharoen et al (2009) estimated that the age of allele Mahidol was 1575 years (63 generations) and the selection coefficient was 0.23. The difference in these estimates may be because they were based on different data, with that of Tishkoff et al (2001) based on microsatellite data and that of Slatkin (2008) based on sequence data.…”
Section: G6pd Deficiencymentioning
confidence: 99%
“…variant that results in moderate G6PD deficiency has undergone recent positive selection in a Karen population in Thailand by conferring resistance against Plasmodium vivax malaria parasites [7]. This positive selection was evidenced by the high frequency of long-range haplotypes [8] around G6PD-Mahidol 487A .…”
Section: Amentioning
confidence: 99%
“…Of the 2,428 individuals, G6PD phenotypes (fluorescent spot test) and genotypes for the 3 most common G6PD variants (Mahidol, Viengchan, and Canton) had already been obtained for 925 individuals, including 415 male individuals [7]. Among these, 188 male individuals agreed to participate in the color blindness assessment.…”
Section: Color Blindness Assessmentmentioning
confidence: 99%
See 1 more Smart Citation